Evaluation of preg-robbing in goldstrike carbonaceous ore using raman spectroscopy - Helm, M.; Vaughan, Jeffrey; Staunton, William (The Canadian of Mining, Metallurgy and Petroleum, 2012)
Samples sourced from the Goldstrike property in Nevada USA, have been evaluated in terms of their preg-robbing capacity and the physical structure of the graphitic carbon component in the carbonaceous gold ore. The study highlights a wide range in preg-robbing capacity between samples collected from the Betze-Post open pit and Rodeo underground mine. The physical structure of the graphitic carbon was assessed using Raman spectroscopy, and is found to play an important role in influencing preg-robbing behaviour. Differences observed in the physical structure of graphitic carbon are thought to be the result of hydrothermal events that occurred at Goldstrike.